2007
DOI: 10.1016/j.jvs.2007.03.052
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for chronic venous disease: The San Diego Population Study

Abstract: Although some risk factors for venous disease such as age, family history of venous disease, and findings suggestive of ligamentous laxity (hernia surgery, flat feet) are immutable, others can be modified, such as weight, physical activity, and cigarette smoking. Overall, these data provide modest support for the potential of behavioral risk-factor modification to prevent chronic venous disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
3
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(107 citation statements)
references
References 43 publications
(81 reference statements)
7
91
3
6
Order By: Relevance
“…Opinions on the relationship between working in prolonged standing or sitting postures and CVD are equivocal. Several authors confirmed such a relationship [4,10,12,13,14], although there were also indications to the contrary [15,16]. In their cross-sectional study, Jawien, Grzela, and Ochwat did not find any relationship between CVD and work in a sitting posture, whereas there was a significantly higher CVD prevalence in women and men working in a prolonged standing posture [9].…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Opinions on the relationship between working in prolonged standing or sitting postures and CVD are equivocal. Several authors confirmed such a relationship [4,10,12,13,14], although there were also indications to the contrary [15,16]. In their cross-sectional study, Jawien, Grzela, and Ochwat did not find any relationship between CVD and work in a sitting posture, whereas there was a significantly higher CVD prevalence in women and men working in a prolonged standing posture [9].…”
Section: Resultsmentioning
confidence: 88%
“…It should cover modified behavior (e.g., watching body weight, not smoking, wearing compression socks or stockings to reduce discomfort and edema), workplace ergonomics (e.g., an adjustable seat, regular exercise to activate the muscular pump of the calf, breaks to rest and stretch legs). Moreover, it is necessary to monitor the course of the disease which, due to competent compensation mechanisms might not particularly manifest itself clinically [14,21,22]. This is especially important if a Doppler examination reveals a more advanced form of CVD localized in the deep system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United States the prevalence of CVI has been estimated at 10% to 35% and the population-based costs at the level of one billion dollars a year [3]. The Edinburg Vein Study, conducted on 1566 men and women aged 18-64 years, demonstrated that 13-year incidence of reflux was 12.7% [4].…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Multiparidade também apresentou um discreto aumento na incidência de varizes em mulheres. Estudos anteriores sugerem que a atividade física seja um fator protetor [7][8][9] .…”
Section: Introdução Introduçãounclassified